Essentials of orthopedic surgery - Wiesel, Sam W.; Delahay, John N. (Springer, 2010)
This concise third edition offers hands-on guidance for identifying and treating the most commonly seen orthopedic problems in children and adults. Convenient as a study source for medical students, its many photographs and illustrations will also serve as a useful clinical reference for young surgeons, residents, nurses, and physician assistants. Each of the many topics is covered in depth and is designed to educate medical students and steer them towards formulating excellent diagnoses and treatment plans. As a further aid, multiple-choice questions are included at the end of each chapter.